Organization of live animal transportation process in the Russian Federation - M. A. Shibayev; I. M. Klinovitskaya; A. V. Belchikhina; A. K. Karaulov (Ветеринария сегодня)
The paper covers the issues of organization of live animal transportation process in the Russian Federation as one of the factors of epidemiological risk associated with the spread of infectious animal disease pathogens. The legal framework, regulating the organization of live animal transportation using different vehicles, as well as quantitative data on live animal movements, taken from state veterinary information system “VetIS” (“Mercury” and “Cerberus” components) were analyzed. The analysis showed that live farmed animals are moved using all transportation means available, motor vehicles, planes, trains, ships as well as by driving. It was established that the major means of transport used to move live animals in the territory of the Russian Federation are motor vehicles. According to the analysis results 4.49 billion animals, including 4.41 billion poultry, 79.8 million large and small ruminants, pigs, horses, fur animals and bees were moved within the country in 2021. At the same time the number of issued veterinary accompanying documents for movements of cattle, poultry and pigs (i.e. in fact the transportations themselves) is much higher than the number of movements of other species. It was revealed that today only the movement of animals by railway is regulated in one way or another. The paper presents the suggestions to introduce the procedures aimed at improvement of biological safety and animal welfare during transportation. The results of the analysis performed can be used to optimize the control of animal transportation in the territory of the Russian Federation by competent authorities.